Experimental Study of Irinotecan Induced Side Effects on Digestive and Immune System of Mice - Liya LIU; Thomas Joseph SFERRA; Senthilkumar SANKARARAMAN; Youqin CHEN (康复学报)
Objective:To investigate irinotecan (CPT-11) -induced side effects on the digestive and immune system of mice.Methods:24 male BABL/c mice were randomly divided into model group (n=12) and control group (n=12). The mice in the model group were given CPT-11 by intraperitoneal injection, the control group were given same volumes PBS by intraperitoneal injection. Body weight, diarrhea index, spleen index, thymus index, complete blood count and pathological changes of the jejunum, ileum and colon were measured on the second day and the fourth day after CPT-11 intervention.Results:Compared with the control group, mice body weight was decreased significantly on the second day and the fourth day upon CPT-11 intervention while diarrhea index was increased (P<0.05); CPT-11 intervention also decreased spleen index, thymus index (P<0.05), white blood cell count and neutrophil count profoundly along with significant jejunum, ileum and colon injury of the mice.Conclusion:CPT-11 can induce side effects about the digestive and immune system, which consistents with the clinical side effects of CPT-11, and this will be helpful for the further development of novel supplementary therapies for CPT-11 induced toxicity.